Analisis Kebutuhan Penerapan PAIKEM Di Sekolah Minggu Pada Jemaat Genesis Wilayah Tobelo Kota - Itje, Tomi; Taliawo, Harun; Saliding, Apriani; May, Oscar Jeferson Scheitzer; Ice, Demianus (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2023)
This research describes the need to apply the active, innovative, creative, effective, and fun learning (PAIKEM) methods in learning in Sunday School at the Evangelical Christian Church in Halmahera (GMIH) Genesis Congregation Tobelo City Region. The method used is qualitative, with observation as a data collection technique. The object of observation is conveying God's word during Sunday School services. The results of the research show that the PAIKEM methods need to be applied in learning at the Sunday School at the Evangelical Christian Church in Halmahera (GMIH) Genesis Congregation, Tobelo City Region because the method used is telling stories or lectures, resulting in Sunday School children quickly getting bored and not focused when learning about the word of God.